Atomic-scale insight into the interactions between hydroxyl radicals and DNA in solution using the ReaxFF reactive force field. (2nd October 2015) - Verlackt, C C W; Neyts, E C; Jacob, T; Fantauzzi, D; Golkaram, M; Shin, Y-K; van Duin, A C T; Bogaerts, A
Abstract: Cold atmospheric pressure plasmas have proven to provide an alternative treatment of cancer by targeting tumorous cells while leaving their healthy counterparts unharmed. However, the underlying mechanisms of the plasma–cell interactions are not yet fully understood. Reactive oxygen species, and in particular hydroxyl radicals (OH), are known to play a crucial role in plasma driven apoptosis of malignant cells. In this paper we investigate the interaction of OH radicals, as well as H2 O2 molecules and HO2 radicals, with DNA by means of reactive molecular dynamics simulations using the ReaxFF force field. Our results provide atomic-scale insight into the dynamics of oxidative stress on DNA caused by the OH radicals, while H2 O2 molecules appear not reactive within the considered time-scale. Among the observed processes are the formation of 8-OH-adduct radicals, forming the first stages towards the formation of 8-oxoGua and 8-oxoAde, H-abstraction reactions of the amines, and the partial opening of loose DNA ends in aqueous solution.